2017
DOI: 10.23965/ajec.42.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Preschool Teachers' and Support Staff's Use and Experiences of Assistive Technology with Children with Disabilities

Abstract: THIS QUALITATIVE CASE STUDY explored the professional philosophies and experiences of preschool teachers and their support staff regarding the use of assistive technology devices (ATDs) in an early intervention inclusive preschool class. Using face-to-face individual interviews as data collection measures, the researchers aimed to understand these practitioners' teaching philosophies and experiences in terms of how they use ATDs with young children with disabilities in their class. A framework analysis of data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
0
11
0
7
Order By: Relevance
“…Similarly, Alkahtani (2013) examined teachers' knowledge and use of AT for students with special educational needs, and indicated teachers' lack of knowledge and skills in using AT, which requires training teachers to increase their overall knowledge about AT. Also, Tamakloe and Agbenyega (2017) explored the experiences of preschool teachers and their support staff about the use of AT devices to support young students with disabilities in an inclusive preschool class. The results indicated a need for professional knowledge and practice in order to impact student learning.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Alkahtani (2013) examined teachers' knowledge and use of AT for students with special educational needs, and indicated teachers' lack of knowledge and skills in using AT, which requires training teachers to increase their overall knowledge about AT. Also, Tamakloe and Agbenyega (2017) explored the experiences of preschool teachers and their support staff about the use of AT devices to support young students with disabilities in an inclusive preschool class. The results indicated a need for professional knowledge and practice in order to impact student learning.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, assistive technologies (AT = devices and software designed specifically for people with disabilities, eg, Tobii DynaVox, Tapit, Picture Exchange Communication System) can have a great impact on many of the educational needs that children present (Al‐Dababneh & Al‐Zboon, 2020; Alkahtani, 2013). Its importance is such that Tamakloe and Agbenyega (2017, p. 32) stated that ‘Assistive technology is the way of the future for all sorts of children with disabilities’. On the other hand, Mohd et al.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the study showed that there are no benefits to the use of tablets as teachers do not use them in the long term. A case study by [25] was designed to explore the perception of preschool teachers using a tablet-application in the classroom to address communication issues with their students. Teachers in the study stated that they preferred and were pleased with the conventional teaching method since it encouraged students to use and present a variety of learning materials at convenient times.…”
Section: Literature Reviewmentioning
confidence: 99%